Detrital zircon record of Mesozoic volcanic arcs in the Lower Cretaceous Mural Limestone, northwestern Mexico. (18th September 2018) - Madhavaraju, Jayagopal; Saucedo‐Samaniego, Julio Cesar; Löser, Hannes; Espinoza‐Maldonado, Inocente Guadalupe; Solari, Luigi; Monreal, Rogelio; Grijalva‐Noriega, Francisco Javier; Jaques‐Ayala, Cesar
Abstract : The northwestern part of Mexico, southern Arizona, and southern California witnessed extensive arc magmatism during Late Triassic to Early Cretaceous. Here, we present results from petrography, whole‐rock geochemistry (major and trace including rare‐earth elements), and detrital zircon geochronological studies that were carried out on sandstones and shales of the Mural Limestone exposed in the Rancho Bufalo area. Based on the petrography, sandstones are classified as sublitharenite, litharenite, feldspathic litharenite, and lithic arkose. The sandstones contain higher proportion of monocrystalline quartz than polycrystalline quartz. Sandstones and shales from the various members of the Mural Limestone show large variations in major and trace elements concentrations. The average concentrations of ΣREE (total ΣREE) are lower in sandstones than in shales. The chondrite‐normalized REE patterns of the sandstones and shales are moderately fractionated with light REE (LREE) enrichment relative to heavy REE (HREE) and with flat to slightly depleted HREE patterns. The chemical index of alteration values and A–CN–K relationships of sandstones indicate low to moderate intensity of weathering in the source region; however, shale samples suggesting the source rocks were subjected to moderate intensity of chemical weathering. The chondrite‐normalized REE patterns, Al2 O3 /TiO2 ratio, elemental ratios like Cr/V, Y/Ni, and Eu‐anomaly (Eu/Eu*), and bivariate plots suggest that the sandstones and shales were derived mainly from felsic source rocks. Detrital zircon U–Pb geochronology of sandstones from Fronteras, Rancho Bufalo, and Cerro La Ceja members of the Mural Limestone show five main groups of detrital zircon age populations: (a) Proterozoic, (b) Palaeozoic, (c) Triassic, (d) Jurassic, and (e) Early Cretaceous. Our study suggests that continental volcanic arcs in northwestern Mexico, southern Arizona, and southern California served as the provenance for the Late Triassic‐Jurassic detritus, whereas the Early Cretaceous zircon grains were derived mainly from the active Alisitos volcanic arc along the northwestern coast of Mexico.